GE_GERICHTE P/20460/2009 vom 10. September 2012 - GE Cour de justice (2012)
; ENCHÈRES ; DROIT CANTONAL ; ERREUR DE DROIT(DROIT PÉNAL) ; ERREUR SUR LES FAITS(DROIT PÉNAL) ; AMENDE | LVVE.5; LVVEE.1; CP.13; CP.21; CP.52; CP.106